AKTIVITAS NITRAT REDUKTASE DAN KANDUNGAN KLOROFIL DAUN PADI HITAM ( Oryza sativa L. kultivar Cempo ireng ) DENGAN PERLAKUAN PUPUK HAYATI - , NICKO AWAN GUMILANG; , Dr. Yekti Asih Purwestri, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Nitrate Reductase Activity (NRA) could be used to assume the productivity of plant because it a had positive correlation with the yield. This research was carried out to study the NRA of Black Rice (Oryza sativa cultivar Cempo Ireng) after application of biofertilizer which contain of Azotobacter sp., Azospirillum sp., and Pseudomonas sp. inoculums. Black rice was planted in mixed medium of soil and manure (3:1) added with 0 mg/pot as control, 20 mg/pot, 30 mg/pot and 50 mg/pot biofertilizer. The NRA of the leaf was analyzed at 6, 8, and 11 weeks after planting by in vivo method using spectrophotometry. The Assay was based on nitrite that formed by the activity of nitrate reductase on NaNO3 substrate. Chlorophyll content and the increase of plant height were also analyzed. Highest NRA (141 mmol/g leaf/ hour) was found in 50 mg/pot of biofertilizer treatment at 6 weeks after planting. The effect of biofertilizer was not significant in chlorophyl content. It could be concluded that 50 mg/pot of the biofertilizer could increase the nitrate reductase activity of black rice (Oryza sativa cultivar Cempo Ireng), but did not affect the chlorophyl content.